Deconstructing the 'older worker': exploring the complexities of subject positioning at the intersection of multiple discourses - Spedale, Simona (Sage, 2018)
This study adopts an intersectional approach to explore the complexities and contingencies of subject positioning in the case of an individual older worker. Five deconstruction strategies are applied to an older worker’s account of his experience of the workplace to unveil the variety of discourses and taken-for-granted assumptions that regulate individual identity formation and contribute to perpetuating the marginalization of the ageing organizational subject. Deconstruction analysis shows how the unique positioning of the research subject emerges at the intersection of complex discourses of age, enterprise, family, death and mental and physical health, casting him as both victim and perpetrator of inequality across a kaleidoscope of interacting categories of oppression. The analysis contributes to the critique of the binary dualism implicit in the victim-perpetrator paradigm dominating mainstream research and policy making on age discrimination in the workplace. It also advocates for new conceptualizations of ageing at work that recognize the systemic nature of inequality as the product of intersecting systems of power relations.